Femmes et habitats périurbains : recompositions de genre à Hô Chi Minh ville - Vincent Berdoulay; Thi Thu Trang Ngô (EchoGéo)
Changes among social relations of men and women are studied in the context of the periurban areas of Ho Chi Minh City. More particularly, three types of habitat (planned, older, makeshift) are surveyed within the district of Binh Tan. There are differences as well as similarities among these types of habitat: They concern the representations of the role and place of women within the family and within society, as well as the particular social practices which were investigated through our survey : the celebration of the ancestors’ worship, the sharing of domestic work, the management of the family’s income, and the decision-making within the family. The results of the survey show that these gendered issues are important in the shaping of the access to resources which can potentially be used by women and which are conditioned by the type of periurban habitat they live in.